ANALISIS KERUSAKAN KONDISI JALAN PANUJAK TANAH AWU KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGARA BARAT MEGGUNAKAN METO BINA MARGA - SOLEMAN LERE WARAT; BAGUS WIDHI DHARMA S.; I GUSTI NGURAH OCTOVA S. (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
This study aims to determine what types of damage are dominant in urban roads in the Praya area and to determine the value of the damage conditions on each of the roads studied and to determine the priority order of road handling and repair. The results of the study were from 1 urban road in Central Lombok Regency which had a total volume of damage of 106 m2. The road segment that has the largest volume of damage is the Panujak Tanah Awu road with cracks of 61 and the groove of 25 with a condition value of 6 and has the smallest priority order of 7, while the road segment with the smallest condition value is 2 Panujak Tanah Awu roads with a priority order of 10